Design and Modeling of Fiber Optical Current Sensor Based on Magnetostriction - (:unkn) unknown (My University, 2017)
A novel fiber optical current sensor (FOCS) which is based on a giant magnetostrictive material, Terfenol-D (T-D) is modeled and prototyped. Several experiments have been conducted to validate the expected results. Magnetostriction is defined as the change in dimensions of a material under the influence of an external magnetic field. The cause of the change in length is due to the rotation and re-orientation of the small magnetic domains in the magnetostrictive material. The magnetostriction of Terfenol-D is modeled and investigated using several software packages. Here, a magnetostriction-based FOCS using a Terfenol-D/epoxy composite is investigated. Particularly, the FOCS is based on applying magnetostrictive composite material to transform an external magnetic field into a corresponding mechanical strain caused by the magnetostriction of the composite. The composite is incorporated in the FOCS for increased durability, flexibility in shape, extended frequency response, and tensile strength compared to monolithic materials. Coupling Terfenol-D with a fiber Bragg grating (FBG) is an excellent method of magnetic field sensing. It consists of an FBG embedded in the composite that converts magnetostrictive strain into frequency chirp of the optical signal in proportion to a magnetic field. This will form a sensor that is compact, lightweight, and immune from electromagnetic interference. For electromagnetic interference mitigation and optimal signal condition, an FBG, which can be easily integrated with an optical fiber network and reflect a narrow band of wavelengths based on grating periods, is used to encode strain information onto an optical signal. This FOCS has potential in detecting power systems faults due to its advantages over the conventional current transformers. Experiments have been performed to investigate the effect of direct current (DC) and alternate current (AC) on the response of the FOCS. Consistent results that indicate its reliability have been obtained. The experiment results matched the predicted response. The effect of the temperature on the response of the FOCS also has been investigated. Finally, future research directions are presented for the enhancement of the FOCS technology.